2017
DOI: 10.3892/mmr.2017.6152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ART1 on the proliferation and migration of mouse colon carcinoma CT26 cells in vivo

Abstract: Arginine-specific mono-ADP-ribosyltransferase 1 (ART1) is an important enzyme that catalyzes arginine-specific mono-ADP-ribosylation. There is evidence that arginine-specific mono-ADP-ribosylation may affect the proliferation of smooth muscle cells via the Rho-dependent signaling pathway. Previous studies have demonstrated that ART1 may have a role in the proliferation, invasion and apoptosis of colon carcinoma in vitro. However, the effect of ART1 on the proliferation and invasion of colon carcinoma in vivo h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…However, the mechanism underlying how high blood glucose levels contribute to the development of CRC is currently unclear. Our previous studies demonstrated that ART1 may promote the proliferation, invasion and metastasis of CRC, and inhibit the apoptosis of CRC in vitro and in vivo (9,29). In addition, it was observed that the expression of ART1 in human CRC tissue from patients with T2DM is much higher than that in non-diabetic CRC tissue (Chen et al, unpublished data).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the mechanism underlying how high blood glucose levels contribute to the development of CRC is currently unclear. Our previous studies demonstrated that ART1 may promote the proliferation, invasion and metastasis of CRC, and inhibit the apoptosis of CRC in vitro and in vivo (9,29). In addition, it was observed that the expression of ART1 in human CRC tissue from patients with T2DM is much higher than that in non-diabetic CRC tissue (Chen et al, unpublished data).…”
Section: Discussionmentioning
confidence: 95%
“…In our previous study, ART1 was revealed to upregulate the expression of p-AKT, c-Myc and c-Fos, in order to promote the proliferation and invasive potential of CT26 cells (9); ART1 also inhibits the apoptosis of CT26 cells via the PI3K/AKT pathway (29). A previous study demonstrated that the PI3K/AKT pathway serves a critical role in promoting aerobic glycolysis (31).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous studies [20,21,22,23] showed high expression of ART1 boosted malignant biological behavior of CRC, besides, ADP-ribosylation was proved to impact glucose metabolism in several pathway [35]. However, there is no research of effect of ART1 on colorectal cancer associated with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…ADP-ribosyltransferase-1 (ART1), an important single ADP ribose transferase, catalyzes the posttranslational modi cation of proteins by transferring a single ADP ribose group to the arginine residue of the protein, is believed to have a closely related to a variety of cellular biological behaviors [18,19]. In the early stage, we reported that ART1 expression changes altered the phosphorylation level of AKT, as well as the activity and expression of mTOR, GSK-3, c-myc, then affected the proliferation, invasion, metastasis, differentiation, angiogenesis and apoptosis of colon cancer CT26 cells [20,21,22]. AKT signaling pathway is one of the important pathways of cell survival, but also the important insulin signaling pathway.…”
Section: Introductionmentioning
confidence: 96%